Digital radiology in skeletal trauma: assessment of casualty officers' performance. - Gillard, J H; Hubbard, C; Das, R; Sherriff, H (Journal of the Royal Society of Medicine, 1998)
Radiographic images can now be produced without the requirement of film processing and development, and can be displayed rapidly on a computer monitor. We assessed junior doctors' performance in interpreting images from 25 patients being investigated for possible fracture and also compared the diagnostic abilities of casualty officers with those of radiology specialist registrars. For interpretation of images viewed at a workstation or as filmed laser images, respectively, sensitivities were 75% and 78%, and specificities were 65% and 76%. These differences were not significant. There was a tendency for radiology specialist registrars to be less specific when reviewing images at a workstation. The demonstration that there is no loss in diagnostic quality when casualty officers interpret fracture images in a purely digitally acquired and viewed format forms a robust basis for economic evaluation of the technology.